2010
DOI: 10.1371/journal.pone.0012103
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenic WAP-T Mouse Mammary Carcinoma Cells: A Model for a Self-Reproducing Homeostatic Cancer Cell System

Abstract: BackgroundIn analogy to normal stem cell differentiation, the current cancer stem cell (CSC) model presumes a hierarchical organization and an irreversible differentiation in tumor tissue. Accordingly, CSCs should comprise only a small subset of the tumor cells, which feeds tumor growth. However, some recent findings raised doubts on the general applicability of the CSC model and asked for its refinement.Methodology/Principal FindingsIn this study we analyzed the CSC properties of mammary carcinoma cells deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 77 publications
2
62
0
Order By: Relevance
“…Despite the recently described cooperation between Slug and Sox 9 in mammary gland [29], we found that cell territories expressing these factors were very distinct in mammary tubules. Sox10 upregulation in SlugKO mice is noticeable considering the basal-like distribution previously reported [35] and the putative role in mammary cell fating [36].…”
Section: Discussionsupporting
confidence: 53%
“…Despite the recently described cooperation between Slug and Sox 9 in mammary gland [29], we found that cell territories expressing these factors were very distinct in mammary tubules. Sox10 upregulation in SlugKO mice is noticeable considering the basal-like distribution previously reported [35] and the putative role in mammary cell fating [36].…”
Section: Discussionsupporting
confidence: 53%
“…A very small fraction of these focal lesions further progresses to invasive, but rarely metastatic mammary carcinomas 3, 4. These SV40‐induced mammary tumors exhibit either a basal‐like, morphologically differentiated phenotype (low‐grade tumors), or an undifferentiated phenotype (high‐grade tumors) featured by coexpression of epithelial and mesenchymal markers, respectively 12. In comparison to other oncoproteins, e.g.…”
mentioning
confidence: 68%
“…Sections from all samples were stained with hematoxylin and eosin (H&E). In order to detect tumor cells in the lung, the lung was cut into serial sections (2 mm) and stained using anti-SV40 T-antigen (T-Ag) antibody (homemade rabbit antibody, R15, 1:20,000 14 ). Sections of all primary tumors (n 5 9-12 per group) were stained using antibodies against vimentin (rabbit monoclonal ab92547, Abcam, Cambridge, UK; 1:500), E-cadherin (rabbit monoclonal #3195, Cell Signaling Technology, Beverly, MA; 1:200), SV40 T-Ag (homemade), F4/80 (rat MCA497EL, AbD Serotec, Oxfordshire, UK; 1:100), CD45 (rat #103102, Biolegend, San Diego, CA; 1:600), Collagen-I (rabbit R1038, Acris; 1:200), alpha smooth muscle actin (rabbit ab5694, Abcam; 1:500) and ECF-L (M2 macrophages; goat #AF2446, R&D systems, Minneapolis, MN; 1:100) as well as the histochemical stainings with H&E, Masson-Goldner trichrome and Picrosirius red.…”
Section: Histologymentioning
confidence: 99%